The effects of a Euro exit on growth, employment, and wages - Riccardo Realfonzo; Angelantonio Viscione (Levy Economics Institute of Bard College, 2015)
A technical analysis shows that the doomsayers who support the euro at all costs and those who naively theorize that a single currency is the root of all evil are both wrong. A euro exit could be a way of getting back to growth, but at the same time it would entail serious risks, especially for wage earners. The most important lesson we can learn from the experience of the past is that the outcome, in terms of growth, distribution, and employment, depends on how a country remains in the euro; or, in the case of a euro exit, on the quality of the economic policies that are put in place once the country regains control of monetary and fiscal matters, rather than on abandoning the old exchange system as such. It all depends on how a country stays in the eurozone, or on how it leaves if need be.
Keywords: F16; F31; F33; G01; 330; Currency Crisis; Devaluation; Employment; Euro Exit; Eurozone; Growth; Income